Metacriticism in Salman Rushdie’s Short Story Yorick - Arıkan, Seda (My University, 2018)
Salman Rushdie is mostly known for his usage of new techniques especially those of postmodernism. In his short story collection East, West, besides many postmodern techniques such as pastiche, parody, and metafiction, his focus on metacriticism is apparent in the short story titled “Yorick”. Rushdie’s “Yorick” that is based on an invented story about the character Yorick, the dead clown whose skull Prince Hamlet handles and makes his famous speech in Hamlet, appears as an example of creative metacriticism that depicts the place and function of literary criticism in a fictional work. Referring to theoretical criticisms of Hamlet, such as psychoanalysis and social theories, Rushdie uses criticism of literary criticism in his short story “Yorick”. Thus, he adds his postmodern interpretation into the analyses of literary criticism since antiquity. This study will firstly focus on the theoretical background of metacriticism, in general, and creative metacritcism, in particular. Later on, it will try to find out the traces of creative metacriticism in Rushdie’s short story “Yorick” in which he also deals with metafiction, the role of the writer, the function of the reader, writer - critic-reader collaboration, the objectivity or subjectivity of literary criticism, creative writing or creative reading, and the truth in storytelling. Analysing how metacriticism operates in the story, finally Rushdie’s ideas on what literary criticism is and should be will be clarified.
Keywords: Edebiyat; Edebi Teori ve Eleştiri